APPLICATION-BASED DIGITAL CONTENT CREATION TRAINING MODEL DEVELOPMENT TO IMPROVE EARLY CHILDHOOD EDUCATORS’ PEDAGOGICAL COMPETENCE IN PANDEMIC TIMES - Ai Masri; Sri Nurhayati (IKIP Siliwangi Bandung, 2024)
Abstract This study examines efforts to enhance the pedagogical competence of Early Childhood Education (ECE) educators. The purpose of this study is to describe the application-based digital content creation training model development and its effect on the pedagogical competence of ECE educators. This research employed research and development techniques (Research and Development), a strategy for creating effective educational products. Interviews, questionnaires, observation of documentation studies, and tests were used to collect data for this study. After data collection, quantitative and qualitative analysis are performed. Quantitative analysis is used to determine the validity of research findings by conducting a series of tests. The training results revealed several findings, including the following: 1) an increase in ECE Educator pedagogical competence, 2) an increase in educator participation in training activities, 3) a high level of motivation for learning, and 4) the establishment of interaction between fellow ECE educators to share learning experiences. Training in the creation of digital content effectively and efficiently through the use of various runs. Thus, the developed application-based digital content creation training model can be used as a substitute model to help ECE educators improve their pedagogical competence in managing online learning during this pandemic period. Keywords: Training, Digital Content, Early Childhood Educators, pedagogical competence